2009
DOI: 10.1111/j.1365-2389.2008.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Indicator of potential residual carbon in soils after exogenous organic matter application

Abstract: An indicator to evaluate the proportion of exogenous organic matter (EOM) remaining in soils over the long-term after application has been developed. A database was constructed with analytical data corresponding to 83 EOMs, including sludges, composts, animal wastes, mulches, plant materials and fertilizers. The data included results of proximal analysis (soluble, SOL, hemicellulose-, HEM, cellulose-, CEL, and lignin-like, LIC, fractions, in g kg-1 total organic matter) and of carbon (C) mineralization during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 36 publications
5
86
0
8
Order By: Relevance
“…However, compost amendment has been shown to increase soil organic carbon content compared to initial soil properties (Ngo et al 2012). Our data indicated that the soil organic matter (OM) and soluble organic carbon (DOC) contents increased significantly following application of fertilizer over a 4-year period; these results are consistent with previous studies that showed increased carbon storage by exogenous organic amendments in addition to improvements in several soil functions related to the presence of organic matter (Lashermes et al 2009;Ngo et al 2012). In the present study, the FT and VP treatments were more conducive to soil carbon conversion and the enhancement of soil microbial activity, because the soil microbes could use DOC more efficiently.…”
Section: Effects Of Vermicompost Application On Soil Propertiessupporting
confidence: 82%
“…However, compost amendment has been shown to increase soil organic carbon content compared to initial soil properties (Ngo et al 2012). Our data indicated that the soil organic matter (OM) and soluble organic carbon (DOC) contents increased significantly following application of fertilizer over a 4-year period; these results are consistent with previous studies that showed increased carbon storage by exogenous organic amendments in addition to improvements in several soil functions related to the presence of organic matter (Lashermes et al 2009;Ngo et al 2012). In the present study, the FT and VP treatments were more conducive to soil carbon conversion and the enhancement of soil microbial activity, because the soil microbes could use DOC more efficiently.…”
Section: Effects Of Vermicompost Application On Soil Propertiessupporting
confidence: 82%
“…Other amendments derived from agriculture include crop residues and SMC. The rate of decomposition of organic amendments and SOC remains in the long term varies with the intrinsic quality of the amendment (Lashermes et al, 2009;Novara et al, 2015). Soil organic matter content is one of the most important soil quality indicators of soil recovery (Mahmoud and Abd El-Kader, 2015;Parras-Alcántara et al, 2015;Pulido Moncada et al, 2015) and is a good sign for soil quality (Gelaw et al, 2015).…”
Section: Soil Organic Carbon (Soc)mentioning
confidence: 99%
“…It is well established that some specific practices, such as organic matter addition (Lashermes et al, 2009), reduced tillage practices (Metay et al, 2009) or crop residues management and permanent cover crops (Rice, 2006), can influence SOC input and its fate in agricultural soils. Without considering specific agricultural practices, the inclusion of information about detailed land use proved to be valuable for explaining observed SOC stocks: the VIM value of the lu3 variable greatly outperformed those of the lu2 and lu1 variables, which are less informative about the land use.…”
Section: Possible Improvements Of the Modelsmentioning
confidence: 99%